Modulating cellular autophagy for controlled antiretroviral drug release. (21st September 2018) - Thomas, Midhun B; Gnanadhas, Divya Prakash; Dash, Prasanta K; Machhi, Jatin; Lin, Zhiyi; McMillan, JoEllyn; Edagwa, Benson; Gelbard, Harris; Gendelman, Howard E; Gorantla, Santhi
Aim: Pharmacologic agents that affect autophagy were tested for their abilities to enhance macrophage nanoformulated antiretroviral drug (ARV) depots and its slow release.Methods: These agents included URMC-099, rapamycin, metformin, desmethylclomipramine, 2-hydroxy-β-cyclodextrin (HBC) and clonidine. Each was administered with nanoformulated atazanavir (ATV) nanoparticles to human monocyte-derived macrophages. ARV retention, antiretroviral activity and nanocrystal autophagosomal formation were evaluated.Results: URMC-099, HBC and clonidine retained ATV. HBC, URMC-099 and rapamycin improved intracellular ATV retention. URMC-099 proved superior among the group in affecting antiretroviral activities.Conclusion: Autophagy inducing agents, notably URMC-099, facilitate nanoformulated ARV depots and lead to sustained release and improved antiretroviral responses. As such, they may be considered for development as part of long acting antiretroviral treatment regimens. Graphical abstract: Nanoformulated antiretroviral therapy (nanoART) enters monocyte-derived macrophages through clathrin-coated pits and are then transported into the cell's early and late endosomes. After treatment with inducers of autophagy, the phagophore sequesters an area of cytoplasm to form double membraned autophagosomes. Lipid conjugation leads to the formation of LC3II associated autophagic vesicles. The late endosome fuses with autophagosomes transferring the nanoART cargo, which in turn fuses with lysosomes leading to the degradation of accumulated cargo. However, if terminal stages are blocked these processes can lead to the accumulation of drug cargos and a slower drug degradation. How, and to what extent, autophagy inducers influence the cell's drug depots is not yet well understood, but likely reflects multiple intracellular mechanisms. URMC-099, a mixed lineage kinase inhibitor, induces autophagy through nuclear translocation of the transcription factor EB. Rapamycin forms complex with FKB12 that specifically acts as an allosteric inhibitor of the mammalian target of rapamycin to speed autophagy. Metformin causes inhibition of the mitochondrial chain complex 1 that in turn indirectly activates AMP-activated protein kinase becoming a negative regulator of mammalian target of rapamycin. Desmethylclomipramine induces autophagy through its abilities to interfere with the autophagic flux by blocking the degradation of the cytoplasmic cargo. Transcription factor EB regulates autophagy and lysosomal biogenesis by 2-hydroxy-β-cyclodextrin. Clonidine induces autophagy through the activation of the Gi signaling pathway that results in the reduction of cAMP levels caused by the inhibition of adenylyl cyclase. All of these autophagy inducers facilitate autophagosome formation that leads to the retention of nanoART in the autophagosome. This ensures the sustained extracellular release of antiretroviral drugs for a prolonged period of time and enhances antiretroviral activities.